Spectroscopic mapping and selective electronic tuning of molecular orbitals in phosphorescent organometallic complexes – a new strategy for OLED materials - Ewen, Pascal R.; Sanning, Jan; Koch, Tobias; Doltsinis, Nikos L.; Strassert, Cristian A.; Wegner, Daniel (Beilstein Journal of Nanotechnology, 2014)
The improvement of molecular electronic devices such as organic light-emitting diodes requires fundamental knowledge about the structural and electronic properties of the employed molecules as well as their interactions with neighboring molecules or interfaces. We show that highly resolved scanning tunneling microscopy (STM) and spectroscopy (STS) are powerful tools to correlate the electronic properties of phosphorescent complexes (i.e., triplet emitters) with their molecular structure as well as the local environment around a single molecule. We used spectroscopic mapping to visualize several occupied and unoccupied molecular frontier orbitals of Pt(II) complexes adsorbed on Au(111). The analysis showed that the molecules exhibit a peculiar localized strong hybridization that leads to partial depopulation of a dz² orbital, while the ligand orbitals are almost unchanged. We further found that substitution of functional groups at well-defined positions can alter specific molecular orbitals without influencing the others. The results open a path toward the tailored design of electronic and optical properties of triplet emitters by smart ligand substitution, which may improve the performance of future OLED devices.
Keywords: charge transfer; density-functional theory; frontier orbitals; hybridization; OLED; Pt(II) complex; scanning tunneling microscopy; scanning tunneling spectroscopy; triplet emitters